Política de educação profissional e tecnológica no Brasil: dualidade estrutural e reformas para a formação profissional na Rede Federal de Ensino - Pereira Júnior, José Nilton Alves (2015)
This paper discusses the current educational policy formation workers under the Federal Professional Education Network. Worries put in the center of the Brazilian society debate as a way to understand what is the place of education in the development of productive forces, their role in the construction of dependent capitalism and how this condition favored the materialization of duality in the education field . Conducted a bibliographical and documentary study, in order to know to what extent the guidelines outlined in the Decree No. 5,154 / 04 and the actions resulting from it are contributing to overcoming the dualist school, that is, the design of vocational training for workers and another for the elite preparatory character. Analysis official documents that guided the educational policies of the past decades has enabled us to understand that the simple repeal of Decree No. 2,207 / 08, separating the high school vocational training, does not guarantee a training onilateral and emancipatory you need the working class.